القطاع الصناعي في سورية ومساهمته في الإيرادات الضريبية - العمار رضوان; ديب شيرين (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف هذا البحث إلى توضيح أهم مؤشرات القطاع الصناعي، ودراسة علاقتها بالإيرادات الضريبية من خلال بيان مساهمة هذه المؤشرات في الإيرادات الضريبية، بالتالي الوصول إلى أهمية القطاع الصناعي ومساهمته في الاقتصاد الوطني. تم استخدام أسلوب تحليل الانحدار لدراسة فرضيات البحث باستخدام البرنامج الإحصائي SPSS 16.0، والمؤشرات المستخدمة هي: الناتج المحلي الإجمالي للقطاع الصناعي، الإنتاج الإجمالي للقطاع الصناعي، مجمل التكوين الرأسمالي للقطاع الصناعي، المستوردات الصناعية، الصادرات الصناعية. توصلت الدراسة إلى انخفاض مساهمة القطاع الصناعي في الاقتصاد ككل وإلى وجود علاقة ضعيفة بين الإيرادات الضريبية وكل من الناتج والإنتاج الإجمالي للقطاع الصناعي، بينما بقية المؤشرات ليس لها أي أثر معنوي على الإيرادات الضريبية خلال الفترة المدروسة. The aim of this research is to clarify the most important indicators of the industrial sector and to study their relation to tax revenues by indicating the contribution of these indicators to tax revenues, thus reaching the importance of the industrial sector and its contribution to the national economy. The regression analysis method was used to study hypotheses using SPSS 16.0. The indicators used are: GDP of the industrial sector, total production of the industrial sector, total capital formation of the industrial sector, industrial imports, industrial exports. The study found that the contribution of the industrial sector to the economy as a whole and to the weak relationship between the tax revenues and the total output and production of the industrial sector, while the other indicators did not have any significant effect on tax revenues during the period studied.